Polish Experiences of Safety Measures Involving Forensic Psychiatric Inpatients Implemented During the SARS-CoV-2 Pandemic - Heitzman, Janusz; Gosek, Paweł (Frontiers in Psychiatry, 2021)
The SARS-CoV-2 pandemic has made it necessary for us to adapt our healthcare systems to a very different sort of reality. This clearly also applies to psychiatric services. The restrictions and safeguards associated with the pandemic particularly concern adherence to social distancing and medical treatment safety procedures. The implementation of these procedures is generally complicated by conditions of forensic psychiatry where, in line with demands made by courts, the treatment and isolation of mentally unwell offenders must be carefully managed. In most countries, forensic psychiatric treatment is an inpatient service where patients are kept in restricted and cramped spaces, making social distancing difficult to implement as patients participate in compulsory group therapeutic activities. As a result, it is necessary to introduce unique recommendations relating to patient safety and treatment adapted to the realities of forensic psychiatry. All this requires the implementation of additional restrictions, over and above those arising from the essential aspects of forensic psychiatry. In this paper, we present and discuss the Polish guidelines for forensic psychiatric care during the SARS-CoV-2 pandemic, developed as a result of discussions on essential measures introduced to reduce the spread of the virus and the unique needs of the forensic patient population.